Miracle in the Qur'an and the gospels : a comparative study - Oladimeji, Ibrahim Abdul-Fatai (Kulliyyah Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, International Islamic University Malaysia, 2010)
A miracle is usually regarded as an extraordinary event which has religious significance in almost all religions of the world. This research work examines and analyzes the meaning, nature, source, role, and function of a miracle. The study is limited to miracles reported in the Qur'ān and the Gospels. In doing so, the parallel and particular features of miracles in both scriptures are underscored, analyzed, and compared. The research also distinguishes a miracle from a wonder of saint (karāmah) as well as from sorcery (sihr). This study involves mainly library research. It engages descriptive, analytical, and comparative methods to examine the miracles reported in both sacred scriptures. The study finds that miracles reported in the Qur'ān and the Gospels share a lot of similarities especially in terms of their role and function as proof of sincerity and truthfulness of the prophets in whose hands a particular miracle is demonstrated. If these similarities are given proper consideration, the religion of Christianity would find Islam does indeed share a wider religious cultural ground with it than many have imagined. This acknowledgment should bring about a much more cordial relationship in modern times between the two monotheistic religions.